Socialization of the Making of PARUS (Ruminant Feed from Sago) and PASI (Utilization of Sago Dregs for Fish) Through the Sago Waste Utilization Integration System (SIPLIS) Towards the Plantation Industry Concept of Sustainability in Green Economy: Sosialisasi Pembuatan PARUS (Pakan Ruminansia dari Sagu) dan PASI (Pemanfaatan Ampas Sagu untuk Ikan) Melalui Sistem Integrasi Pemanfaatan Limbah Sagu (SIPLIS) Menuju Konsep Industri Perkebunan Sustainability in Green Economy - Harmaidi, Desma; Rahmah, Anania; Qurthuby, Muhammad; Putri, Vivin Jenika; Putra Juliansyah, Muhammad Ridho; Angraini Jelita (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Feed is important for the survival of livestock, limited feed can affect livestock production and reproduction. One solution to overcome limited feed is to utilize agricultural waste. The potential of Sago dregs can be used as an economical and easy to obtain material so that Sago dregs can be used to make PARUS and PASI. This service activity was carried out with the aim of providing socialization and procedures for processing sago dregs into PARUS and PASI. This activity was carried out in Bagan Melibur Village, Merbau District, Meranti Islands Regency, Riau Province. The results obtained from the socialization activities on the Optimization of Making PARUS (Ruminant Feed from Sago) and PASI (Utilization of Sago Dregs for Fish) within the framework of the Sago Waste Utilization Integration System (SIPLIS), sago dregs can be processed into animal feed at an affordable price. This initiative not only contributes to increasing community income and environmental sustainability, but also creates new job opportunities in the local area.